Monoterpenoid indole alkaloid dimers from Kopsia arborea inhibit cyclin-dependent kinase 5 and tau phosphorylation. (November 2022) - Chen, Chen; Liu, Jian-Wen; Guo, Ling-Li; Xiong, Feng; Ran, Xiao-Qian; Guo, Ya-Rong; Yao, Yong-Gang; Hao, Xiao-Jiang; Luo, Rong-Can; Zhang, Yu
Abstract: Three undescribed monoterpenoid indole alkaloid dimers (kopoffines A-C, which are connected via a methylene unit) and with nine known alkaloids were isolated and identified from the fruits of Kopsia arborea Blume. Their structures, including their absolute configurations, were established by HRESIMS, NMR, single-crystal X-ray diffraction, and ECD analyses. Kopoffines A-C showed significant inhibition against cyclin-dependent kinase 5 (IC50 : 0.34–2.18 μM). Western blotting analyses showed that kopoffines A-C significantly decreased the protein levels of CDK5 and phospho-CDK5 (Tyr15) (pCDK5) at concentrations of 2.5 and 10 μM. The levels of phospho-Tau (Thr217) (pTau217, a new biomarker of AD), and phospho-Tau (Ser396) (pTau396), which play major roles in the formation of neurofibrillary tangles, were decreased by the kopoffines A-C treatment. Molecular docking studies indicated that kopoffines A-C could form stable interactions with CDK5. Graphical abstract: Three undescribed monoterpenoid indole alkaloids were isolated from the fruits of Kopsia arborea . They showed significantly inhibition against cyclin-dependent kinase 5 and tau phosphorylation, which indicated they had the potential for therapy of AD. Image 1 Highlights: Three undescribed indole alkaloids were isolated from Kopsia arborea. Kopoffines A-C are indole alkaloids dimers connected via a methylene unit. Kopoffines A-C showed significant inhibition against cyclin-dependent kinase 5. Kopoffines A-C can significantly decrease protein levels of CDK5 and phospho-CDK5. Kopoffines A-C can decrease the levels of phospho-Tau (Thr217 and Ser396).